2010
DOI: 10.1038/jp.2010.115
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal resuscitation for the preterm infant: evidence versus practice

Abstract: In an effort to determine the actual conduct of neonatal resuscitation and the errors that may be occurring during this process, we developed a method of video recording neonatal resuscitations as an ongoing quality assurance project. We initiated video recordings of resuscitations using simple video recorders attached to an overhead warmer and reviewed the resultant tapes during biweekly quality improvement meetings. We also added the continuous recording of analog information such as heart rate, oximeter val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 78 publications
1
51
0
1
Order By: Relevance
“…25,33,[40][41][42] Clinicians in ED, neonatology, and trauma care have implemented real-time video capture of resuscitation events in the clinical environment as part of local quality programs. [43][44][45][46][47][48][49][50][51] Nadler et al 25 demonstrated that including video recordings of neonatal resuscitations in debriefings improved teamwork in future neonatal resuscitations. The simulation literature is more mixed, with a meta-analysis demonstrating that video-assisted debriefing has negligible and nonsignificant effects on timerelated skills.…”
Section: Debriefing In the Emergency Department After Clinical Eventsmentioning
confidence: 99%
“…25,33,[40][41][42] Clinicians in ED, neonatology, and trauma care have implemented real-time video capture of resuscitation events in the clinical environment as part of local quality programs. [43][44][45][46][47][48][49][50][51] Nadler et al 25 demonstrated that including video recordings of neonatal resuscitations in debriefings improved teamwork in future neonatal resuscitations. The simulation literature is more mixed, with a meta-analysis demonstrating that video-assisted debriefing has negligible and nonsignificant effects on timerelated skills.…”
Section: Debriefing In the Emergency Department After Clinical Eventsmentioning
confidence: 99%
“…The reliance on chest rise to assess the optimal tidal volume is difficult and inaccurate. 28 About two thirds of the participants routinely try nasal continuous positive airway pressure in babies with less severe respiratory distress as a means to avoid intubation in the DR. This practice can be supported by two recent randomized controlled trials, at least in terms of the feasibility of using nasal continuous positive airway pressure as an alternative to combined intubation and surfactant for even extreme preterm infants.…”
Section: Discussionmentioning
confidence: 99%
“…o xygen supplementation is one of the most common therapeutic interventions in resuscitation and neonatal intensive care of term and preterm infants (1). However, both hypoxia and hyperoxia must be avoided because of their detrimental effects on morbidity and mortality in these children.…”
mentioning
confidence: 99%